2006
DOI: 10.1016/j.prp.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of septal fibrosis of the liver. (An experimental study with a new model.)

Abstract: Septal fibrosis is an important, frequent, and non-specific type of fibrosis associated with chronic liver diseases, but its pathogenesis is still poorly understood. An interesting model of septal fibrosis occurs in rats infected with the nematode Capillaria hepatica. This model was used to investigate the pathogenesis, site of origin, structure, and cell-types of septal fibrosis. Forty young adult Wistar rats were inoculated with 800 embryonated eggs of C. hepatica. Daily liver samples were obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The present study demonstrates that expression of VEGF-A is up-regulated in liver fibrosis, and its expression is increased in activated HSCs [5], [6], [8], [9]. Rosmorduc et al showed that biliary cirrhosis is associated with hepatocellular hypoxia in experimental models[8].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present study demonstrates that expression of VEGF-A is up-regulated in liver fibrosis, and its expression is increased in activated HSCs [5], [6], [8], [9]. Rosmorduc et al showed that biliary cirrhosis is associated with hepatocellular hypoxia in experimental models[8].…”
Section: Discussionsupporting
confidence: 58%
“…Vascular endothelial growth factor (VEGF) is considered to be the central angiogenic factor during chronic liver injury. The present study demonstrates that expression of VEGF-A is up-regulated during liver fibrosis, and its expression is increased in activated hepatic stellate cells (HSCs) [5], [6], [8], [9].…”
Section: Introductionmentioning
confidence: 66%
“…The process of septal fibrosis begins with the extension of the septa between central veins through interhepatocellular space and the space of Disse on the sides of the sinusoids [22] . As fibrosis proceeds, capillarization and then venularization occurs [22] , [23] . During this process, the fenestrations in some hepatic sinusoids are lost and the development of basal laminae occur alongside the collagenization of the extravascular spaces of Disse [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Se han desarrollado algunos estudios utilizando la variedad Wistar de R. norvegicus infectada experimentalmente con C. hepatica como modelo animal, para investigar la patogénesis, el sitio de origen, la estructura y los tipos de células involucrados en la fibrosis de los tabiques (31)(32)(33)(34)(35). Asimismo, existen pruebas de una asociación significativa entre la hepatitis inducida por la infección de C. hepatica y la hipertrofia arteriolar pulmonar en roedores, que puede representar efectos de hipertensión pulmonar y llegar a afectar otros órganos como el corazón y el riñón (20).…”
Section: Discussionunclassified